ITech in library instruction: tips and best practices. Issue 1 (7th March 2016) - Eng-Ziskin, Susanna; Johnson, Jamie
Abstract : Purpose: – This paper aims to describe some best practices and tips for librarians who will be teaching in iPad classrooms. Design/methodology/approach: – California State University Northridge librarians recently began teaching information literacy sessions to freshmen seminar students in a dedicated iPad classroom. Prior to this, they scoured the literature to find information on how to use the iPads to enhance their instruction. The kinds of papers they were looking for did not seem to exist so they began a process of trial and error during their instruction sessions to formulate their own best practices which are enumerated in this paper. Findings: – A list of best practices for teaching information literacy sessions with iPads. Originality/value: – This paper will be of value to instruction librarians who will be teaching in iPad or tablet classrooms. A search of the library literature shows there are no similar articles with practical tips and best practices for librarians.